2021
DOI: 10.1002/stc.2711
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization of electromagnetic tuned inerter damper for structural vibration suppression

Abstract: Summary A novel dual‐functional inerter‐based damper, called electromagnetic tuned inerter damper (ETID), is presented in this paper for vibration control and energy harvesting. To evaluate the effectiveness of the ETID, the simplified model of ETID coupled with a single‐degree‐of‐freedom (SDOF) structure has been established. The H2 optimal design of the ETID‐SDOF system has been conducted, whose goal is to minimize the value of the root mean square (RMS) of the displacement and absolute acceleration of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As usually done in the relevant literature for design issues, the adequate space to accommodate the TMD stroke is critical to guarantee the proper functioning of the devices 27,31–35,39–44 . Furthermore, the knowledge of the stroke length value leads to an estimate of the cost of both the spring and the damper connecting the two masses.…”
Section: Resultsmentioning
confidence: 99%
“…As usually done in the relevant literature for design issues, the adequate space to accommodate the TMD stroke is critical to guarantee the proper functioning of the devices 27,31–35,39–44 . Furthermore, the knowledge of the stroke length value leads to an estimate of the cost of both the spring and the damper connecting the two masses.…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al 56 proposed an EM resonant shunt TMDI (ERS-TMDI), and their numerical results demonstrated that the inerter improved the control effectiveness of the ERS-TMD. Luo et al 57 also conducted parametric optimization of an EM-TID for controlling structural vibration. Salvi and Giaralis 58 proposed an energy harvesting-enabled TMDI, which comprises a TMD system, a linear motor, and an inerter.…”
Section: Noveltymentioning
confidence: 99%
“…proposed an EM resonant shunt TMDI (ERS‐TMDI), and their numerical results demonstrated that the inerter improved the control effectiveness of the ERS‐TMD. Luo et al 57 . also conducted parametric optimization of an EM‐TID for controlling structural vibration.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Apart from the mechanical approaches, the hydraulic mechanism 18,19 is also adopted, which can achieve the inertial effect by enlarging the piston area or by decreasing the channel cross-section area. Furthermore, by means of electromagnetic approach, 20,21 the circuit composed of capacitors, inductors, and resistors assembled in a proper arrangement can also be used to offer an equivalent inertial effect in the mechanical device. Given the large inertial coefficient, the work efficiency of the vibration absorber is greatly improved, which helps to enhance the capacity of vibration control system.…”
Section: Introductionmentioning
confidence: 99%